2022
DOI: 10.1101/2022.03.01.22271618
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vitro Characterization of SARS-CoV-2 Protein Translated from the Moderna mRNA-1273 Vaccine

Abstract: Extensive research around mRNA vaccines and their proposed utility during the current COVID-19 pandemic resulted in many publications concerning the SARS-Cov-2 spike protein and angiotensin converting enzyme-2 receptor-binding domain of the virus, but none describe the characteristics of the full-length protein obtained from the modified/synthetic mRNA that is part of the Moderna and Pfizer-BioNTech vaccines. In this paper, we provide the first data characterizing the actual proteins produced by mouse and huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Although it has not been peer reviewed, a study by Veenstra et al (2022) addresses this astounding regulatory disaster, over a year after billions of doses had been injected into arms. As the authors write, there has been "extensive research around mRNA vaccines and their proposed utility…but none describe the characteristics of the full-length protein obtained from the modified/synthetic mRNA that is part of the Moderna and Pfizer-BioNTech vaccines.…”
Section: "Autoimmune" Political Attacks On Regulation and Quality Con...mentioning
confidence: 99%
“…Although it has not been peer reviewed, a study by Veenstra et al (2022) addresses this astounding regulatory disaster, over a year after billions of doses had been injected into arms. As the authors write, there has been "extensive research around mRNA vaccines and their proposed utility…but none describe the characteristics of the full-length protein obtained from the modified/synthetic mRNA that is part of the Moderna and Pfizer-BioNTech vaccines.…”
Section: "Autoimmune" Political Attacks On Regulation and Quality Con...mentioning
confidence: 99%
“…Another consideration could be the size of the protein that needs to be coded by mRNA. Full S spike protein coded by the mRNA vaccines is about 180 kDa, whereas the mRNAs used in protein replacement therapy so far code for proteins in the range of 27–127 kDa as seen in Table 1 [ 139 , 140 ]. Should the need arise for longer mRNAs, delivery vector design can be revisited to be able to accommodate bigger constructs and deliver them efficiently.…”
Section: Conclusion and Future Applicationsmentioning
confidence: 99%
“…SARS-CoV-2 is one of the Beta coronavirus strains which was identified in Wuhan, China in December 2019 for the first time (1)(2)(3) . After entering the body, SARS-CoV-2 binds to its receptor via the 180-KD spike protein (4)(5)(6). The studies showed that the angiotensinconverting enzyme-2 (ACE-2) on host cells acts as a high-affinity receptor for SARS-CoV-2 (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%